Instrument Analysis of Biology Teachers' Needs to Assess Students' Creative Thinking Skills Using RASCH Model - Sari, Rezqi Rohmatika; Sugiharto, Bowo; Widoretno, Sri (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aimed to investigate the validity, reliability, scale understanding, item difficulties, and bias items of the instrument for analyzing the needs of biology teachers regarding the assessment of creative thinking skills using the RASCH model. The instrument was modified based on the indicators of divergent and convergent thinking processes in the scientific learning stages integrated with the dimensions of creative thinking skills by using ADDIE research model. The research participants comprised of 104 participants from the Solo Raya area, those of whom were 64 Senior High School Biology teachers and 40 Junior High School Science teachers. The research instrument used inventory with a Likert scale of 1 to 4. The instrument validity, reliability, scale understanding, item difficulties, and bias items were analyzed by applying the RASCH model using Winstep 3.73. The research results showed that the overall validity was acceptable, and the item validity did not need improvement. Overall reliability was very good, and the item reliability was excellent. Rating scale analysis showed respondents had understood the Linkert scale of 1 to 4 well. Based on the item difficulties results of the teachers' responses, it was found that there had not been any teachers who evaluated the indicators of creative thinking skills by using writings or pictures in problem-solving assessment. The bias test results on the instrument items indicated that five items could potentially be biased due to age difference, and the two others were due to gender type. Therefore, the development of assessment instruments for creative thinking skills with scientific and social problem-solving based assignments, as well as writing and visual expressions, is required.